Thermal degradation in methylammonium-formamidinium-guanidinium lead iodide perovskites - Minussi, F. B. [UNESP]; Silva, R. M. [UNESP]; Carvalho, J. F.; Araújo, E. B. [UNESP] (Royal Society of Chemistry (RSC), 2024)
The stability of hybrid halide perovskites (HPs) is one of the main factors hindering their potential commercial application. Numerous environmental agents are known to degrade HPs and their devices, including temperature, which can cause chemical modifications even at operational temperatures. Thermal degradation has been the subject of major studies in pure and HP-related compounds that have paved the way for a deep understanding of the phenomenon. However, thermally induced modifications in mixed-cation HPs have not been addressed in detail yet. In the present work, we report a systematic study of thermal degradation over a wide range of compositions of methylammonium lead iodide (MAPbI3) partially substituted by guanidinium (GA+) and formamidinium (FA+), using diverse experimental techniques and thermal treatment conditions. The results indicated that mixed-cation HPs were more stable than pure MAPbI3. Thermal degradation followed the volatilization of MA+ and MA+-related chemical species with PbI2 consequently appearing; however, GA+-rich compositions could suffer from an additional degradation pathway by the segregation of non-perovskite GAPbI3, reducing the material's thermal stability. This process also provoked a change in the degradation kinetic law. Remarkably, the simultaneous substitution with FA+ inhibited the formation of GAPbI3, even in compositions with high GA+ contents. Our work advances the crucial understanding of thermal degradation processes and how to increase the thermal stability of halide perovskites.